THE IMPACT OF EXPERIENTIAL MARKETING ON ENHANCING CUSTOMER SATISFACTION IN KOPITAGRAM BEKASI CITY - Wiarsih Febriani (Asosiasi Dosen Muda Indonesia, 2023)
The more coffee shops that provide coffee drinks, the more competition there is, where many coffee shops provide various kinds of coffee flavors, unique and creative places for customer comfort and satisfaction. To face this competition, a marketing concept can be used, namely experiential marketing, with this concept customers can differentiate between one coffee shop and another because Individuals have the opportunity to acquire firsthand experience employing a sensory, tactile, interactive, relational, and cognitive approach. The primary research technique involved gathering data directly through the distribution of questionnaires to 100 respondents who are customers of Kopitagram Bekasi. Analytical tools such as the Likert scale, Acceptedity test, reliability test, correlation, determination, t-test, and f-test were applied. Based on the outcomes of the conducted analysis, it is deduced that Experiential Marketing, which consists of the Five Senses, Feelings, Thinking and Action variables, has a partial and simultaneous influence on satisfaction with Kopitagram Bekasi.